Analisis Prakseologi Buku Ajar Bahasa Arab Madrasah Tsanawiyah Kelas IX - Abdul Azziz Maulana; Shofa Musthofa Khalid (Universitas Nahdlatul Wathan Mataram, 2026)
Arabic textbooks play a crucial role in learning; however, improper material presentation and task design can trigger learning obstacles. Given the limited evaluation of textbooks using a praxeological approach, this study aims to analyze the ninth-grade Madrasah Tsanawiyah Arabic textbook published by the Directorate of KSKK of the Ministry of Religious Affairs of the Republic of Indonesia, as well as to identify the characteristics of Arabic task design from a praxeological perspective. This study employs a descriptive qualitative method with a library research design. The data were sourced from the tarkib (grammar) material in Chapter 1, which was analyzed using Yves Chevallard's praxeological framework through four components: task, technique, technology, and theory. The results indicate that the didactic design in this textbook features a structured development of the praxis dimension, but it does not align with the consistency of the logos dimension. Despite systematic instructional progress, the absence of definitive written instructions in the initial phase and the fluctuating presentation of theoretical foundations trigger various learning obstacles, including didactic, epistemological, and ontogenic obstacles. This gap causes students to lean toward mechanical pattern memorization without comprehensive logical understanding. Therefore, a stricter synchronization between task assignments and theoretical explanations is required from the very beginning of the material to ensure students' conceptual maturity in mastering Arabic grammar